Female mice exposed to low doses of dioxin during pregnancy and lactation have increased susceptibility to diet-induced obesity and diabetes - Myriam P. Hoyeck; Rayanna C. Merhi; Hannah L. Blair; C. Duncan Spencer; Mikayla A. Payant; Diana I. Martin Alfonso; Melody Zhang; Geronimo Matteo; Melissa J. Chee; Jennifer E. Bruin (Elsevier, 2020)
Objective: Exposure to persistent organic pollutants is consistently associated with increased diabetes risk in humans. We investigated the short- and long-term impact of transient low-dose dioxin (2,3,7,8-tetrachlorodibenzo-p-dioxin, TCDD) exposure during pregnancy and lactation on glucose homeostasis and beta cell function in female mice, including their response to a metabolic stressor later in life. Methods: Female mice were injected with either corn oil (CO; vehicle control) or 20 ng/kg/d TCDD 2x/week throughout mating, pregnancy and lactation, and then tracked for 6-10 weeks after chemical exposure stopped. A subset of CO- and TCDD-exposed dams was then transferred to a 45% high-fat diet (HFD) or remained on a standard chow diet for an additional 11 weeks to assess the long-term effects of TCDD on adaptability to a metabolic stressor. To summarize, female mice were transiently exposed to TCDD and then subsequently tracked beyond when TCDD had been excreted to identify lasting metabolic effects of TCDD exposure. Results: TCDD-exposed dams were hypoglycemic at birth but otherwise had normal glucose homeostasis during and post-TCDD exposure. However, TCDD-exposed dams on a chow diet were modestly heavier than controls starting 5 weeks after the last TCDD injection, and their weight gain accelerated after transitioning to a HFD. TCDD-exposed dams also had an accelerated onset of hyperglycemia, impaired glucose-induced plasma insulin levels, reduced islet size, increased MAFA-ve beta cells, and increased proinsulin accumulation following HFD feeding compared to controls. Overall, our study demonstrates that low-dose TCDD exposure during pregnancy has minimal effects on metabolism during the period of active exposure, but has detrimental long-term effects on metabolic adaptability to HFD feeding. Conclusions: Our study suggests that transient low-dose TCDD exposure in female mice impairs metabolic adaptability to HFD feeding, demonstrating that dioxin exposure may be a contributing factor to obesity and diabetes pathogenesis in females.